2020
DOI: 10.1212/wnl.0000000000010343
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of benign paroxysmal positional vertigo with vitamin D supplementation

Abstract: ObjectiveTo assess the effect of vitamin D and calcium supplementation in preventing recurrences of benign paroxysmal positional vertigo (BPPV).MethodsWe performed an investigator-initiated, blinded-outcome-assessor, parallel, multicenter, randomized controlled trial in 8 hospitals between December 2013 and May 2017. Patients with confirmed BPPV were randomly assigned to the intervention (n=518) or the observation (n=532) group after a successful treatment with canalith repositioning maneuvers. The primary out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 35 publications
0
52
0
5
Order By: Relevance
“…On these bases, vitamin D supplementation has been suggested to decrease recurrent attacks of BPPV. Interestingly, some recent prospective, randomized, and controlled trials have indicated a preventive effect of vitamin D supplementation on the occurrence rate of BPPV [59]. Based on this evidence vitamin D supplementation may be considered in patients with frequent relapses of BPPV and reduced vitamin D serum levels.…”
Section: Benign Paroxysmal Positional Vertigo (Bppv)mentioning
confidence: 99%
“…On these bases, vitamin D supplementation has been suggested to decrease recurrent attacks of BPPV. Interestingly, some recent prospective, randomized, and controlled trials have indicated a preventive effect of vitamin D supplementation on the occurrence rate of BPPV [59]. Based on this evidence vitamin D supplementation may be considered in patients with frequent relapses of BPPV and reduced vitamin D serum levels.…”
Section: Benign Paroxysmal Positional Vertigo (Bppv)mentioning
confidence: 99%
“…A significant reduction in the recurrences was found in the treatment group (Fig. 1a) [73]. A subsequent meta-analysis of six randomized trials also proved the preventive effect of vitamin D supplementation on recurrences of BPPV ( Fig.…”
Section: Treatmentsmentioning
confidence: 66%
“…As prevention of recurrence of BPPV, and with limited rationale, in preventing severe forms of COVID-19, vitamin D3 is used to a greater extent worldwide, due to its low level in the general population, and also very small side effects [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%